2010
DOI: 10.1682/jrrd.2009.09.0148
|View full text |Cite
|
Sign up to set email alerts
|

Rollator use and functional outcome of geriatric rehabilitation

Abstract: Abstract-In a quasi-experimental pre-and postdesign, we examined the effect of rollator use on functional rehabilitation outcome in geriatric patients. From a sample of 458 geriatric inpatients, we matched 30 subjects who were not using assistive devices in their everyday lives but received a wheeled walker at the time of hospital admission (first-time user group) according to their admission scores on three motor performance tests (Timed Up-and-Go, Five-Times-Sit-to-Stand, and Performance-Oriented Mobility As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The specific aims of rollator use vary depending on the patient diagnosis. For example, in the elderly or patients with neurological disease such as multiple sclerosis, rollators are used to increase walking endurance and muscle strength or to improve balance (Chee et al, 2013;Vogt et al, 2010;Braun et al, 2014). Following surgery, reduced weight bearing or pain may be treatment goals (Smith et al, 2012), whereas in patients with chronic obstructive pulmonary disease improvement of functional exercise capacity and reduction of dyspnoea can be the objectives (Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The specific aims of rollator use vary depending on the patient diagnosis. For example, in the elderly or patients with neurological disease such as multiple sclerosis, rollators are used to increase walking endurance and muscle strength or to improve balance (Chee et al, 2013;Vogt et al, 2010;Braun et al, 2014). Following surgery, reduced weight bearing or pain may be treatment goals (Smith et al, 2012), whereas in patients with chronic obstructive pulmonary disease improvement of functional exercise capacity and reduction of dyspnoea can be the objectives (Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…General use during rehabilitation proves to improve confidence and restore or maintain motor ability at the highest possible level. A study in [13] showed that walker assistance does not interfere with rehabilitation outcome and in some cases may decrease the rehabilitation period. The study was based on subjective observations of walker users.…”
Section: Aging Walkers and Physiotherapymentioning
confidence: 99%
“…Studies about rollators revealed that these devices are safe and stable, providing an increase in confidence, as well as an improvement in balance and mobility (Kegelmeyer et al, 2013;Liu, 2009;Vogt et al, 2010). This AD also causes a lower variability in gait and it is easy to use (Kloos et al, 2012;Vogt et al, 2010;Wellmon et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This AD also causes a lower variability in gait and it is easy to use (Kloos et al, 2012;Vogt et al, 2010;Wellmon et al, 2006). On the other hand, there are Volume 31, Number 3, p. 208-217, 2015 several authors indicating that this AD causes changes in posture and, an increased risk of fall (Kegelmeyer et al, 2013;Liu et al, 2009;Vogt et al, 2010). However, on this study forearm supports were added to the device in order to give more stability to the gait, better posture and increased support (Ishikura, 2001;Martins et al, 2013;Youdas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%